Impact of a Digital Diabetes Prevention Program on Risk Factors for Chronic Disease in a Workforce Cohort. Issue 12 (December 2020) - Birse, Charles E.; Shiffman, Dov; Satish, Anita; Fragala, Maren S.; Arellano, Andre R.; Sweet, Cynthia M. Castro; Lagier, Robert J.
Abstract : Objective: Evaluate the effect of a digital Diabetes Prevention Program (dDPP) on chronic disease risk factors in a workplace population. Methods: dDPP participants were employees and spouses with BMI ≥ 24 kg/m 2 and prediabetes or diabetes ( n  = 84). Annual change in risk factors before and after dDPP were assessed in the dDPP group and in a retrospectively identified matched control group drawn from those who participated in a dDPP after the conclusion of this study ( n  = 252). Results: In the dDPP group, body weight, BMI, fasting glucose, triglycerides, total cholesterol and LDL-cholesterol decreased in the post-dDPP period compared with the pre-dDPP period ( P  < 0.05). In the control group, no difference between the annual change before and after dDPP was observed ( P  > 0.37). Conclusion: The dDPP was effective in reducing risk factors for chronic disease in a workplace setting. Abstract : Supplemental Digital Content is available in the text